2009
DOI: 10.1108/03056120910953268
|View full text |Cite
|
Sign up to set email alerts
|

A direct‐writing approach to the micro‐patterning of copper onto polyimide

Abstract: Access to this document was granted through an Emerald subscription provided by emerald-srm:198285 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 56 publications
(84 reference statements)
1
12
0
Order By: Relevance
“…Metals 2017, 7, 189 2 of 12 [6,13,[24][25][26][27][28]. Sputtering can produce a dense and uniform metallic layer with good adhesion on PI, but the high-vacuum operational environment makes cost-down difficult to achieve.…”
Section: Metallization Process Of Pimentioning
confidence: 99%
See 2 more Smart Citations
“…Metals 2017, 7, 189 2 of 12 [6,13,[24][25][26][27][28]. Sputtering can produce a dense and uniform metallic layer with good adhesion on PI, but the high-vacuum operational environment makes cost-down difficult to achieve.…”
Section: Metallization Process Of Pimentioning
confidence: 99%
“…Recently, wearable and portable technologies have attracted considerable attention because multiple functions such as communication, internet, sensor, navigation, and media, can be integrated in a small and light-weight device [1][2][3][4][5][6][7][8][9]. The rapid development of wearable and portable devices has driven the microelectronic industries to develop new technologies to meet the demands of scale miniaturization and multi-functionality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These methodologies are based on processes such as laser-based thermally induced deposition, laser-assisted surface modification for subsequent electroless deposition, and laser-assisted photocatalysis-mediated deposition, among others. [1,5] Some examples include the patterning of micron-sized platinum features using a continuous-wave (cw) argon ion laser (λ ¼ 514 nm) to induce the thermal decomposition of platinum metal-organic films coated onto quartz substrates for subsequent electroless plating. [6] In contrast, the selective activation of diamond substrates with a Cu vapor laser (λ ¼ 510 nm) and KrF excimer laser (λ ¼ 248 nm) was also reported.…”
Section: Introductionmentioning
confidence: 99%
“…Micro moulding of a sol‐gel‐derived precursor resulted in the selective growth of the nanorods. Ng et al (2009) reported a direct laser writing approach to deposit micro‐patterned metal onto polymer. Here, a metal source is first doped into the substrate in the form of ions and a continuous wave HeCd laser was used for the reduction of metal ions allowing fine resolution of feature size.…”
Section: Introductionmentioning
confidence: 99%